Effects of graphene nanoplatelets and reduced graphene oxide on poly(lactic acid) and plasticized poly(lactic acid): a comparative study - Chieng, Buong Woei; Ibrahim, Nor Azowa; Wan Yunus, Wan Md. Zin; Hussein, Mohd Zobir; Then, Yoon Yee; Loo, Yuet Ying (MDPI, 2014)
The superlative mechanical properties of graphene-based materials make them the ideal filler materials for polymer composites reinforcement. Two types of graphene-based materials, graphene nanoplatelets (xGnP) and reduced graphene oxide (rGO), were used as nanofiller in poly(lactic acid) (PLA) polymer matrix, as well as plasticized PLA. The addition of rGO into PLA or plasticized PLA substantially enhanced the tensile strength without deteriorating elasticity, compared to xGnP nanocomposites. In addition, the investigation of the thermal properties has found that the presence of rGO in the system is very beneficial for improving thermal stability of the PLA or plasticized PLA. Scanning electron microscope (SEM) images of the rGO nanocomposites display homogenous and good uniformity morphology. Transmission electron microscopy (TEM) images revealed that the rGO remained intact as graphene sheet layers and were dispersed well into the polymer matrix, and it was confirmed by X-ray diffraction (XRD) results, which shows no graphitic peak in the XRD pattern.